Composite analysis of impacts of dust aerosols on surface atmospheric variables and energy budgets in a semiarid region of China. Issue 6 (25th March 2014) - Ling, Xiaolu; Guo, Weidong; Fu, Congbin
Abstract Loess Plateau is one of the dust aerosol source regions featured by its sandy underlying surface and affected significantly by dust events. In order to investigate climatic forcing of dust aerosols in semiarid region, continuous observations of particulate matter (PM10 concentration), meteorological elements, and energy fluxes were collected at Semiarid Climate Observatory and Laboratory in northwestern China from March to May during 2007–2010. The result shows that dusty days are often evoked under the condition when a strengthening trough is combined with the development of strong convection. During dusty days, the frequency of northerly winds increases significantly with the average wind velocity to be around 4.0 m/s; temperature is low during the daytime and high at nighttime. Relative humidity and surface pressure, however, are about 15% and 70% lower than average in dusty days, respectively. Energy balance closure is typically poor in dusty days. During daytime, the downward/upward solar radiation at land surface is less in dusty days than in nondusty days with the largest difference of 206.7 W/m2 and 33.25 W/m2, respectively. Difference in downward longwave radiation between dusty and nondusty days is 35 W/m2, accounting for 11.7% and 14% of the daily mean for dusty and nondusty days, respectively. The net radiation flux, as well as sensible/latent heat fluxes at surface is smaller during the daytime but larger at nighttime in dusty days. The maximum differences of sensible/latent heat fluxes between dusty and nondusty days can reach for 41.9% and 12.1% of the maximum net radiation, respectively.